2013
DOI: 10.1093/ndt/gft034
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-protective effects of azelnidipine versus a diuretic in combination with olmesartan in hypertensive patients with diabetes and albuminuria: a randomized study

Abstract: Azelnidipine is equally effective as a thiazide diuretic in reducing urinary albumin when used in combination with olmesartan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Another recent study 17 demonstrated the non-inferiority of the antialbuminuric effect of azelnidipine, another so-called “renoprotective” CCB 18, compared with the thiazide diuretic, trichloromethiazide. Because several different mechanisms have been attributed to the “renoprotective” CCBs (e.g., T-type calcium channel blockade (benidipine), N-type calcium channel blockade (benidipine and cilnidipine), and sympatholytic effects (azelnidipine)), the extent of antialbuminuric action might be different among these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study 17 demonstrated the non-inferiority of the antialbuminuric effect of azelnidipine, another so-called “renoprotective” CCB 18, compared with the thiazide diuretic, trichloromethiazide. Because several different mechanisms have been attributed to the “renoprotective” CCBs (e.g., T-type calcium channel blockade (benidipine), N-type calcium channel blockade (benidipine and cilnidipine), and sympatholytic effects (azelnidipine)), the extent of antialbuminuric action might be different among these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 8 RCTs recruited Asian subjects only, [ 13 15 , 18 , 20 , 21 , 23 , 24 ] while the other 6 RCTs were conducted in either mixed-race or unmentioned-race populations. Six RCTs compared the 2 combined treatments in 1001 patients with diabetes mellitus, [ 13 , 14 , 16 , 17 , 22 , 25 ] and 3 RCTs compared treatments in 1079 CKD patients. [ 19 , 23 , 24 ] Regarding the sample size, ACCOMPLISH (11,506 patients) and COLM (5141 patients) were the 2 largest RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies obtained Jadad scores lower than 3, [ 15 , 16 , 18 , 20 , 24 ] indicating low quality. The Cochrane Collaboration assessment suggested that 8 studies were at a high risk of bias [ 12 , 14 16 , 18 , 20 , 23 , 24 ] (Table 1 ). The main reason for the high risk was the lack of detailed descriptions of concealing, randomization, or allocation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation